An unusual insectivore assemblage from the early Miocene of southwestern Europe: The talpids and dimylids from the Ribesalbes–Alcora Basin (Spain) - Crespo Roures, Vicente Daniel (2019)
The Miocene record of talpids and dimylids in south-western Europe is very scarce. In the present work, we study for the first time the talpids and complete the description of the dimylids, already started with a new species of the genus Plesiodimylus from the Ribesalbes–Alcora Basin (MN4, lower Aragonian, early Miocene) by Crespo et al. (2018). The talpids recovered inRibesalbes–Alcora comprise themost common Desmanodon daamsi and Desmanella fejfari, for which the last known occurrence is recorded here. The dimylids comprise the species Plesiodimylus ilercavonicus, which expands the biostratigraphic record of the genus and species and has been found in a new site. On the other hand, we discuss the palaeoecological significance of this assemblage.